Irrigation, lakes and myths of origin - Sherbondy, Jeanette (1982)
My interest in the use of groundwater for irrigation in Cusco led me to investigate the context in which this issue is discussed in the Andes. It is said that the water for the Tambo Machay canal comes from Lake Coricocha through an underground canal built by the Incas, this lake is also considered the source of water for several other rivers and irrigation systems. Although features of artificial underground channels are found in the Huatanay Valley, the connection between Coricocha and the Tambo Machay channel is neither natural nor artificial. There is simply no connection.